Surgical Management of Peyronie's Disease With Co-Existent Erectile Dysfunction. Issue 4 (18th September 2019) - Krishnappa, Pramod; Fernandez-Pascual, Esau; Carballido, Joaquin; Moncada, Ignacio; Lledo-Garcia, Enrique; Martinez-Salamanca, Juan Ignacio
Abstract: Introduction: Surgical intervention in Peyronie's disease (PD) should ideally be delayed until the resolution of acute inflammatory phase. Aim: The objective of this review was to highlight the results of penile prosthesis to correct refractory erectile dysfunction (ED) in patients with PD, and the secondary procedures that may be required to correct the penile curvature. Methods: A systematic search on PubMed online database using Preferred Reporting Items for Systematic Reviews and Meta-Analyses recommendations was done using the MeSH terms "Peyronie's disease" and "erectile dysfunction." Main Outcome Measure: Success and satisfaction rates of various procedures. Results: The search yielded 324 language-specific (English and Spanish language) articles and 58 articles were retained for final review. The following variables were assessed in different studies: number of patients, types of secondary procedure to correct the curvature, satisfaction rates, and follow-up period. Conclusion: The aim of the surgery in PD should be to achieve a functionally straight penis (<20 degree curvature) with good erection. Patients with refractory ED in PD are candidates for penile prosthesis. Secondary procedures, like manual modeling, plication, plaque incision, or excision grafting, may be required depending on the degree of penile curvature and penile length. In quest for the best graft, TachoSil graft seems to have gained popularity in Europe.